Let f : ( 1 , ∞ ) → ( 0 , ∞ ) be a continuous decreasing function with x → ∞ lim f ( 8 x ) f ( 4 x ) = 1
Then
x → ∞ lim f ( 8 x ) f ( 6 x ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Just to say that f is decreasing so the inequalities should be reversed
nice solution
I think you forgot x inside each function
Visualise f as f ( x ) = 1 / l o g ( x ) as it satisfies D f , R f , the decreasing nature and
x → ∞ lim l o g 8 x l o g 4 x = x → ∞ lim l o g 8 + l o g x l o g 4 + l o g x = x → ∞ lim l o g 8 / l o g x + 1 l o g 4 / l o g x + 1 = 1
Similarly we can show that,
x → ∞ lim l o g 8 x l o g 6 x = 1 .
Its the sandwich theorem..
Problem Loading...
Note Loading...
Set Loading...
Since f is a continuous decreasing function,
f ( 8 ) ≤ f ( 8 ) f ( 8 ) ≤ ⟹ x → ∞ lim f ( 8 ) f ( 8 ) ≤ x → ∞ lim 1 ≤ x → ∞ lim f ( 6 ) ≤ f ( 4 ) f ( 8 ) f ( 6 ) ≤ f ( 8 ) f ( 4 ) f ( 8 ) f ( 6 ) ≤ x → ∞ lim f ( 8 ) f ( 4 ) f ( 8 ) f ( 6 ) ≤ 1
By squeeze or sandwich theorem , we have: ⟹ x → ∞ lim f ( 8 ) f ( 6 ) = 1